2006
DOI: 10.1021/bi0604936
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillation of Human Insulin A and B Chains

Abstract: Human insulin, which consists of disulfide cross-linked A and B polypeptide chains, readily forms amyloid fibrils under slightly destabilizing conditions. We examined whether the isolated A and B chain peptides of human insulin would form fibrils at neutral and acidic pH. Although insulin exhibits a pH-dependent lag phase in fibrillation, the A chain formed fibrils without a lag at both pHs. In contrast, the B chain exhibited complex concentration-dependent fibrillation behavior at acidic pH. At higher concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 45 publications
9
82
0
2
Order By: Relevance
“…6A) (8,9,27). A similar competitive mechanism was reported previously for amyloidogenic light chains (37,38), ␤2m (39), insulin (40), and ␣-synuclein (41,42), in which the aggregation process was branched, with one pathway leading to fibrils and another to oligomeric intermediates that may ultimately form amorphous aggregates. Miti et al (17) recently reported a similar mechanism with hen egg white lysozyme at pH 2 and 52°C including various stable, metastable, and kinetically trapped amyloid aggregate phases.…”
Section: Competitive Model Of Amyloid Fibrillation and Amorphoussupporting
confidence: 76%
“…6A) (8,9,27). A similar competitive mechanism was reported previously for amyloidogenic light chains (37,38), ␤2m (39), insulin (40), and ␣-synuclein (41,42), in which the aggregation process was branched, with one pathway leading to fibrils and another to oligomeric intermediates that may ultimately form amorphous aggregates. Miti et al (17) recently reported a similar mechanism with hen egg white lysozyme at pH 2 and 52°C including various stable, metastable, and kinetically trapped amyloid aggregate phases.…”
Section: Competitive Model Of Amyloid Fibrillation and Amorphoussupporting
confidence: 76%
“…This is an important mechanism of aggregate growth in some polypeptide systems that readily form large fibrils (lengths $microns). 45,50,52,53 Independent of whether aggregates are fibrillar, if they are insoluble this often results in visually apparent precipitate, particulate, or haze formation. 9,54-56…”
Section: Aggregation Kinetics and Shelf Lifementioning
confidence: 99%
“…33,48,49,67,68 Aggregation With Condensation Condensation effects manifest in primarily two qualitatively distinct ways: (i) precipitate or particulate formation; 9,36,54-56 (ii) aggregateaggregate association creating high-MW, soluble aggregates and gels. 45,50,52,53,69 In the former situation, aggregate concentrations in solution are either saturated or remain low and at local steady state because the rate of creation of new soluble aggregates is balanced by the rate at which aggregates precipitate from solution. 21,36,59 As a result, the kinetics of growth and condensation do not significantly affect the rate of conversion of monomer to aggregate, and the kinetics of monomer loss under native-favoring conditions are well described by Eqs.…”
Section: Aggregation By Nucleation and Growthmentioning
confidence: 99%
“…Ещё одним интересным направлением при разработке препаратов инсулина является введение D-и L-замен [16]. Считается, что D-аминокислоты увеличивают активность инсулина.…”
Section: введение D-и L-заменunclassified
“…Такие изменения являются более критичными для связывания с рецептором, поскольку, в отличие от мутаций в N-конце А-цепи, влияют на природную и "переходную" (необходимую для связывания с рецептором) конформации. Кроме того, известно, что дисульфидная связь A20-B19 является наиболее значимой для образования специфического ядра фолдинга [16], в связи с чем введение мутаций в С-конец А-цепи является нежелательным.…”
unclassified